Pengaruh Kecerdasan Emosional, Servant Leadership, dan Komitmen Organisasi terhadap Organizational Citizenship Behavior di PT.ABC - Sellya Alma; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The purpose of this study is to establish the relationship between PT.ABC's organizational citizenship behavior and intelligence, servant leadership, and organizational commitment. This is a quantitative study conducted with the use of SPSS Statistics. A total of eighty PT.ABC employees were selected using the approach of purposive sampling. This study's measurement scale is a Likert scale. The measuring instrument is a paper-based and Google Forms-based survey. According to the findings of this study, emotional intelligence has a positive influence on organizational citizenship behavior, servant leadership has a positive influence on organizational citizenship behavior, organizational commitment has a positive influence on organizational citizenship behavior, and emotional intelligence, servant leadership, and organizational commitment all have a positive influence on organizational citizenship behavior simultaneously. The benefits of PT ABC's research will enhance organizational citizenship through emotional intelligence, servant leadership, and organizational commitment.